2021
DOI: 10.3390/ijerph18042021
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Roles of Sensation Seeking and Worry among Nature-Based Adventure Tourists

Abstract: The adventure tourism subsector continues to be popular today. Both industry and academia define adventure tourism’s scope from either the physical (e.g., outdoor activity and physical activity) or psychological aspects (e.g., thrill seeking and challenges). Recent studies have pointed out that adventure tourism can be interpreted differently across cultures and markets. Still, risk has always been universally accepted as an essential characteristic of adventure tourism. Thus, most empirical research has studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Further, SS and risk-taking behavior were observed in individuals (Jonah, 1997) having extreme motivational preferences, and when unable to locate something fascinating they got bored (Piko et al , 2017). SS is determined as a frequently seen personality attribute (López-Bonilla and López-Bonilla, 2012) that creates positivity generating of novel ideas, exposure to experience and RPI (Afaq et al , 2020; Kiatkawsin et al , 2021). Prevailing literature indicates that customers with higher levels of SS are often attracted to outdoor adventure, sports like skiing and snowboarding (Demircan, 2019; Taheri and Thompson, 2020), holiday preferences (Yıldırım and Çakici, 2020) and stopover destination (Wang et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, SS and risk-taking behavior were observed in individuals (Jonah, 1997) having extreme motivational preferences, and when unable to locate something fascinating they got bored (Piko et al , 2017). SS is determined as a frequently seen personality attribute (López-Bonilla and López-Bonilla, 2012) that creates positivity generating of novel ideas, exposure to experience and RPI (Afaq et al , 2020; Kiatkawsin et al , 2021). Prevailing literature indicates that customers with higher levels of SS are often attracted to outdoor adventure, sports like skiing and snowboarding (Demircan, 2019; Taheri and Thompson, 2020), holiday preferences (Yıldırım and Çakici, 2020) and stopover destination (Wang et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fourth, it investigates the indirect effect of CVCC on CE and C-RPI to develop a unique customer experience (Abid et al , 2022). Fifth, the indirect effect of sensation seeking (SS) as moderator is incorporated to assess its effect on CE and CVCC (Kiatkawsin et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Generically stated, adventure leisure activities utilize interactions with the natural environment that contain elements of real or apparent danger, in which the outcome can be influenced by the participant and circumstances [ 31 ]. The development of adventure parks can be attributed to the so-called commodification of adventure tourism [ 32 ], a phenomenon that implied a switch from activities that were perceived as high-risk, high-difficulty, and usually reserved for those with advanced skills, to a choreographed and packaged set of more accessible leisure activities, with diluted associated risk. As a result, in an adventure park, all the activities are aimed at minimizing the objective risk, conferring a relatively safe environment, ensuring a safety–risk balance, and, at the same time, offering adrenaline-fueled experiences [ 1 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, previous studies have found that personal influence or private selfconsciousness can be influenced by social forces [72][73][74][75]. In other words, an individual's personal motivation is often shaped by the external environments [61,73,[75][76][77].…”
Section: Hedonic Effectmentioning
confidence: 99%
“…Furthermore, previous studies have found that personal influence or private selfconsciousness can be influenced by social forces [72][73][74][75]. In other words, an individual's personal motivation is often shaped by the external environments [61,73,[75][76][77]. Evidence from previous studies includes how expectations from parents and how the social image of successful people ultimately influence an individual to pursue education or lifestyle activities [12,16,22,78].…”
Section: Hedonic Effectmentioning
confidence: 99%